EVALUATION OF SOME LENTIL VARIETIES UNDER SPRINKLER AND DRIPPING IRRIGATION SYSTEMS IN NEWLY RECLAIMED SANDY SOIL - & El-Housini, Khattab (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
Two field experiments were carried out during winter seasons 2014/2015 and 2015/2016 at the Research and Production Station, National Research Centre, El-Nubaria Province, El-Behira Governorate, Egypt. The main objective of this study is to evaluate growth, yield and yield component of some lentil varieties (Giza 29, Giza 51, Giza 9, Giza 370 and Giza 4) under different irrigation system (sprinkler and dripping irrigation). Results were showed that Giza 29 produced the highest 100 seed weight (1.50 gm), seed yield (1.23 ton/ha) and harvest index 2.34%, however Giza 51 recorded the highest number of pods and seed yield/plant. Furthermore, Giza 9 recorded the highest number of branches and biological yield (1.25 ton/ha), however either Giza 370 Giza 4 and had the lowest values of the same traits. Also the results revealed that Giza 29 recorded the highest values of chemical contents. Concerning the effect of irrigation system, result were highlighted that drip irrigation system significantly increased all of the studied characters, while sprinkler irrigation system produced the lowest values for all the studied characters.